TANGGUNG JAWAB PT RAILINK TERHADAP KETERLAMBATAN PENUMPANG KERETA API BANDARA - Tasia Eda Lestari; Amad Sudiro (Jurnal Hukum Adigama, 2019)
Transportation in Indonesia has experienced very rapid development, one of which is in land transportation, namely airport trains managed by PT Railink. But in the airport railroad operations there are also problems, namely delays. One of the incidents that occurred was the delay of the airport train with train number 7160 which caused passengers to miss flight schedules and could not fly that day. There is no law that discusses airport railroad, so the Act used still refers to the railroad regulations in general, namely Law 23 of 2007. So the author discusses how PT Railink's responsibility for the delay of airport train passengers. The author uses normative legal methods, interview data and survey results as supporting data. The government has issued a new regulation namely the Minister of Transportation's Regulation of the Republic of Indonesia Number PM 63 of 2019 concerning Minimum Service Standards for Transportation of People by Train, but in this regulation it has not been able to provide sufficient legal protection for passengers for airport train delays.